2018
DOI: 10.1093/mnras/sty1287
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the circum-galactic medium of damped Lyman-α absorbing galaxies

Abstract: Gas flows in and out of galaxies through their circumgalactic medium (CGM) are poorly constrained and direct observations of this faint, diffuse medium remain challenging. We use a sample of five z ∼ 1-2 galaxy counterparts to Damped Lyman-α Absorbers (DLAs) to combine data on cold gas, metals and stellar content of the same galaxies. We present new HST/WFC3 imaging of these fields in 3-5 broadband filters and characterise the stellar properties of the host galaxies. By fitting the spectral energy distribution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 95 publications
2
18
0
Order By: Relevance
“…In Fig.8 we present the H i column density versus impact parameter. Studies so far, mostly for high H i column density absorbers (Krogager et al 2017;Augustin et al 2018), showed an anti-correlation between N(H i) and impact parameter, which is also reproduced by the OWLS hydrodynamical simulations (Rahmati & Schaye 2014): the larger the N(H i) column densities the smaller the impact parameter. Including all galaxies associated with absorbers, we are retrieving this relation also at lower H i column densities (from 10 18 to 10 21.7 cm −2 ).…”
Section: Absorbers Are Associated With Multiple Galaxiessupporting
confidence: 53%
“…In Fig.8 we present the H i column density versus impact parameter. Studies so far, mostly for high H i column density absorbers (Krogager et al 2017;Augustin et al 2018), showed an anti-correlation between N(H i) and impact parameter, which is also reproduced by the OWLS hydrodynamical simulations (Rahmati & Schaye 2014): the larger the N(H i) column densities the smaller the impact parameter. Including all galaxies associated with absorbers, we are retrieving this relation also at lower H i column densities (from 10 18 to 10 21.7 cm −2 ).…”
Section: Absorbers Are Associated With Multiple Galaxiessupporting
confidence: 53%
“…Similar conclusions were also reached with deep ground-based imaging of sub-DLA hosts, which suggest that these systems preferentially sample more luminous -and therefore more massive galaxies than DLAs (Meiring et al 2011). By measuring the stellar mass of the absorbing galaxies from matching spectral energy distribution galaxy templates to photometry, Augustin et al (2018) and Rhodin et al (2018) directly confirmed the apparent anti-correlation between the host's stellar mass and the H i column-density of the absorber. If real, this correlation is remarkable as we expect both high-and low column-density LOS to pass through a given galaxy.…”
Section: A Redshift Evolution In the Mean Impact Parametersmentioning
confidence: 56%
“…Moreover, this relation can be interpreted as a relation between DLA metallicity and host galaxy halo mass (Møller et al 2013), reflecting the known luminosity-selected galaxy mass-metallicity relation (Tremonti et al 2004;Maiolino et al 2008). By measuring the stellar masses of the host galaxies, we now know that DLAs indeed follow a mass-metallicity relation (Christensen et al 2014;Augustin et al 2018;Rhodin et al 2018).…”
Section: Introductionmentioning
confidence: 91%